Effects of Apple Polyphenols and Taurine on Growth Performance, Tissue Morphology, and Lipid and Glucose Metabolism in Rice Field Eel (Monopterus albus) Fed High Oxidized Fish Oil - Shanshan Wu; Jiamin Li; Yao Deng; Peng Fang; Wei Lei; Ao Luo; Zhengwei He; Liufeng Xiong; Gang Yang; Vikas Kumar; Mo Peng (Aquaculture Nutrition)
The aim of this trial was to investigate the effects of apple polyphenols (AP) and taurine (TA) on the growth performance, tissue morphology, and lipid and glucose metabolism in rice field eel fed diets with high oxidized fish oil (OFO). A 10-week feeding experiment was conducted using juveniles (initial body weight 16.66 ± 0.02 g) fed five different diets. Three diets were formulated with various levels of OFO at 9.5, 600, and 800 meq·kg−1 and named as Control, POV600, and POV800 diet, respectively. The other two diets were POV600 and POV800 supplemented with 0.5% AP and 0.2% TA, respectively. Compared to the Control group, only the eels fed POV800 exhibited an increase in weight gain and specific growth rate along with a reduction in feed conversion ratio. AP and TA did not affect growth performance; juveniles fed AP, however, showed a decrease in liver weight. Both POV600 and POV800 decreased nuclei number and increased vacuoles size in the liver. POV800 damaged the intestinal structure integrity and reduced goblet cells number. AP repaired the liver damage on nuclei number and vacuoles size in fish fed with POV600 diet, while TA mitigated intestinal histopathological damage on intact structure and goblet cells number. The mRNA expression level of liver ampkα in fish fed AP was upregulated, while dietary TA upregulated the mRNA expression levels of liver ampkα and accα. In the muscle, POV600 downregulated mRNA expression levels of accα, cpt1, and lipin, whereas POV800 upregulated mRNA expression levels of accα, pparα, and lipin. Dietary AP and TA could counteract the effects of POV600 and POV800 diet on muscle lipid metabolism. Both POV600 and POV800 diets upregulated mRNA expression levels of liver pck1 and gsk3α. AP and TA both downregulated mRNA expression level of liver pck1, while only TA downregulated the expression of liver gsk3α. AP increased the mRNA expression level of gsk3α in muscle. In summary, inclusion of AP and TA did not affect growth performance but showed a potential to alleviate liver or intestinal damages induced by a high OFO diet. Dietary AP and TA were also found to regulate mRNA expression of genes related to lipid and glucose metabolism.